2013
DOI: 10.1111/sltb.12024
|View full text |Cite
|
Sign up to set email alerts
|

Patient Suicide: The Experience of Flemish Psychiatrists

Abstract: The experience of the most distressing patient suicide on Flemish psychiatrists is described. Of 584 psychiatrists, 107 filled a self-report questionnaire. Ninety-eight psychiatrists had been confronted with at least one patient suicide. Emotional suffering and impotence were the most common feelings reported. Changes in professional practice were described and included a more structured approach to the management of suicidal patients. Colleagues and contact with the patient's family were the most frequently u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
47
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 35 publications
7
47
4
Order By: Relevance
“…In Trimble et al’s () study the most commonly reported emotional reactions for psychologists to a client's suicide were sadness, shock, helplessness, guilt and anger. Such grief reactions were consistent with American studies on psychologists and psychiatrists (Chemtob, Hamada, Bauer, Kinney, & Torigoe, ; Chemtob et al, ), therapists (Hendin, Lipschitz, Maltsberger, Haas, & Wynecoop, ), social workers (Ting, Sanders, Jacobson, & Power, ), and most recently, Flemish psychiatrists (Rothes, Scheerder, Audenhove, & Henriques, ), and mental health practitioners in Switzerland (Dransart, Gutjahr, Gulfi, Didisheim, & Séguin, ).…”
supporting
confidence: 82%
See 4 more Smart Citations
“…In Trimble et al’s () study the most commonly reported emotional reactions for psychologists to a client's suicide were sadness, shock, helplessness, guilt and anger. Such grief reactions were consistent with American studies on psychologists and psychiatrists (Chemtob, Hamada, Bauer, Kinney, & Torigoe, ; Chemtob et al, ), therapists (Hendin, Lipschitz, Maltsberger, Haas, & Wynecoop, ), social workers (Ting, Sanders, Jacobson, & Power, ), and most recently, Flemish psychiatrists (Rothes, Scheerder, Audenhove, & Henriques, ), and mental health practitioners in Switzerland (Dransart, Gutjahr, Gulfi, Didisheim, & Séguin, ).…”
supporting
confidence: 82%
“…Trimble et al () found that two of the most helpful coping strategies for psychologists were speaking to colleagues and/or supervisors. These findings have coincided with a number of other studies which have also revealed the importance of social support from colleagues and supervisors following the suicide of a client (Chemtob et al, ; Chemtob et al, ; Dransart et al, ; Gaffney et al, ; Grad, Zavasnik, & Groleger, ; Hendin et al, ; Kleespies, Smith, & Becker, ; Rothes et al, ).…”
supporting
confidence: 82%
See 3 more Smart Citations